Controlling effect of source-reservoir assemblage on natural gas accumulation: A case study of the upper triassic xujiahe formation in the sichuan basin - Tan, Kaijun; Yao, Jun; Chen, Juan; Tang, Dahai; Qin, Yang; Wu, Qingpeng (Frontiers in Earth Science, 2022)
The enrichment law of tight sandstone gas in the Upper Triassic Xujiahe Formation in the Sichuan Basin has not been fully revealed. In this study, the controlling effect of source-reservoir assemblage on gas accumulation in the Xujiahe Formation was systematically studied. The results show that pores and fractures are developed in the tight sandstone reservoirs of the Xujiahe Formation. The main pore types are intragranular dissolved pores and intergranular pores. The quality of sandstone reservoirs in the Xujiahe Formation is controlled by sedimentation, diagenesis and tectonic processes. Underwater distributary channels and estuary bars are favorable microfacies for reservoir development, and chlorite cemented facies and dissolution-kaolinite cemented facies are the most favorable diagenetic facies. The fractures formed in the Himalayan period can significantly improve the permeability of the reservoir. In addition, the natural gas composition and carbon isotope characteristics of the Xujiahe Formation are significantly different in different intervals of the same gas field and the same interval of adjacent gas fields. This shows that the natural gas has no obvious vertical mixing and lateral migration, and it has the distribution characteristics of "discontinuous and relatively independent". Then, the natural gas will be preferentially charged in the feldspar lithic sandstone and feldspar quartz sandstone with large thickness and good physical properties by means of short-range migration. According to the research, the hydrocarbon supply capacity of the single layer in each interval is weak, and it leads to the low filling degree of the gas reservoir and the insufficient separation of gas and water. On the whole, four sets of extra-source "lower generation and upper storage" assemblages and two sets of "self-generation and self-storage" source-reservoir assemblages are developed in the Xujiahe Formation. The development scale of natural gas is mainly controlled by the type of source-reservoir combination, and the areas with close source-reservoir contact and high hydrocarbon generation intensity are high-quality reservoir development areas.